The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1988
DOI: 10.1016/0014-2999(88)90708-x
|View full text |Cite
|
Sign up to set email alerts
|

o-Methoxy-sila-hexocyclium: a new quaternary M1-selective muscarinic antagonist

Abstract: The musearlnie receptors are currently divided into at least three subtypes: M 1 , M 2 a and M 2 ß (for recent reviews, see Eglen and Whiting, 1986; Mutschier et al., 1987;1988). M 1 -Receptors are found in high density in neuronal tissues such as autonomic ganglia, cerebral cortex and hippocampus, whereas M 2 -receptors are mainly present in lower brain areas and in peripheral effector organs such as heart (M 2 a) and smooth musdes (M 2 ß) as weil as glands (M 2 ß). Their different affinities for selective m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
6
0

Year Published

1989
1989
2005
2005

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 3 publications
4
6
0
Order By: Relevance
“…In the present study 60 p.g/rat was the highest dose of methoctramine tested, as we observed that administration of 100 p.gjrat plus carbachol 1 p.g pro- Melchiorre et al (1987), c Lambrecht et al (1988a). d Lambrecht et al (1988c). c Lambrecht et al (1988b), r Eltze (1988), and 1 Eglen and Whiting (1986).…”
Section: Effect Of Muscarinic Antagonists On Carbacho/-induced Drisupporting
confidence: 55%
“…In the present study 60 p.g/rat was the highest dose of methoctramine tested, as we observed that administration of 100 p.gjrat plus carbachol 1 p.g pro- Melchiorre et al (1987), c Lambrecht et al (1988a). d Lambrecht et al (1988c). c Lambrecht et al (1988b), r Eltze (1988), and 1 Eglen and Whiting (1986).…”
Section: Effect Of Muscarinic Antagonists On Carbacho/-induced Drisupporting
confidence: 55%
“…M1 receptors are above all found in the nervous system and are characterized by a high affinity for pirenzepine Birdsall et al, 1980;Brown et al, 1980;Hammer & Giachetti, 1982;Lambrecht et al, 1988b). M2 receptors, which show low affinity for pirenzepine, have been further subdivided into cardiac type and glandular/ smooth muscle subtypes by use of selective antago-1 Author for correspondence.…”
Section: Introductionmentioning
confidence: 99%
“…The M1 subtype exhibits a high affinity toward pirenzepine and o-methoxy-silahexocyclium (see Eglen & Whiting, 1986 for review;Lambrecht et al, 1988); the M2 subtype exhibits a high affinity toward methoctramine (Michel & Whiting, 1988) and the M3 subtype exhibits a high affinity toward hexahydrosiladiphenidol and silahexocyclium (Mutschler et al, 1987). The anatomical location of these subtypes suggest that the cerebral cortex, heart and salivary gland possess a preponderance of M1, M2 and M3 receptors respectively (Doods et al, 1987).…”
mentioning
confidence: 99%